An Investigation into the Determinants of U.S. Strike Activity - Tracy, Joseph S. (American Economic Review, 1986)
This paper outlines the construction of a new panel data set of U.S. contract negotiations and strike activity. This is the first to contain data on both strikes and contract expirations. Key findings are that 15 percent of scheduled negotiations end as strikes, but strike probabilities are higher in June and lower in December; the variability, and not the level, of firm profitability affects strike activity; personal characteristics of the union workforce affect strike activity; and strikes are more likely when the local labor market is tight, but less likely when the industry labor market is tight.